ACEH BERDUKA (Analisis Program pemberitaan i-News TV malam) - Hanafi . (ArtComm, 2020)
This research uses a critical discourse analysis method, from Fair Clough and the value of Islamic communication which not only analyzes the literature discourse but also describes the aspects of description, analysis, and interpretation of the overall coverage. The results of the study provide an explanation of the interpretation of the coverage of i-News TV evening, titled "Aceh Grieving" in the midst of media openness, especially private television programs that tend to be free, as well as the sentiment of media crews in manifesting their roles and functions in the public sphere. Several findings conclude, how the media construct the contents of the news, which shows to the people of Indonesia, that the MNC group, with i-News TV is a mass media that has social sensitivity and social responsibility (CSR) in Indonesia. The approaches taken by the media include: a) Economically and businessly; news content invites the public to care socially-economically, will be moved to channel material donations (money) voluntarily. Here later the MNC Group appears to be one of the names of national private media institutions which in reality are able to channel community social assistance funds to Aceh, b) Ideologically and Politically; to strengthen and posisitioining organizations like this for a mass media communication becomes potential and is expected later, indirectly, can reap political benefits and opportunities associated with moral support and engagement of political interests of the wider community, c) from a cultural approach; Aceh is culturally and historically the region where the people were first touched by the movement to spread Islam in the archipelago.